I want to be ready : improvised dance as a practice of freedom - Goldman, Danielle (University of Michigan Press, 2010)
I Wam to Be Ready to Original research, careful readings of individual performances, and a thorough knowledge of dance scholarship to offer an understanding of the "freedom" of improvisational dance. While scholars often celebrate the freedom of improvised performances, they are generally focusing on freedom from formal constraints. Drawing on the work of Michel Foucault and Houston Baker, among others, Danielle Goldman argues that this negative idea of freedom elides improvisation's greatest power. Far from representing an escape from the necessities of genre, gender, class, and race, the most skillful improvisations negotiate an ever shifting landscape of constraints. This work will appeal to those interested in dance history and criticism and also to interdisciplinary audiences in the fields of American and cultural studies.